Pencegahan Covid-19 Melalui Edukasi PHBS Pada Masyarakat Dusun Moncongloe Bulu, Kabupaten Maros - Sainah, Sainah Iin; Sumaryanti, Sumaryanti; Sofyan, Sofyan (Universitas Patria Artha, 2021)
The aim of this community service is to immediately educate people on the importance of living a clean and healthy lifestyle (PHBS) to protect Covid-19. To prevent Covid-19, the method used is theory-based education and practice PHBS with three stages, namely preparation, implementation, and evaluation. Residents of Saliong Village, Moncongloe Bulu RT 15 District, Buru Regency are the recipients of this community service activity. As a result of this community service activity, residents of Moncongloe Bulu Village gain knowledge through the theory and practice -based education stages on how to be aware of and deal with Covid-19, how to apply PHBS and types of high protein foods and drinks, how to use masks (differentiate between disposable and reusable masks), and how to wash your hands properly. Residents of Moncongloe Bulu Village will be able to live a clean and healthy lifestyle as a result of this education, such as knowing how to wash their hands correctly and adequately, how to use masks (knowing the types of disposable masks and types of re-washing masks), avoiding direct contact with other residents, and complying with health protocols, establishing a pattern and behavior of healthy living in the community through the consumption of healthy nutritious food, regular exercise, and routine health checks at the nearest Health Service Center.Keywords: PHBS, Covid-19, Health Promotion